Robotic Approach to Creation of Continent Catheterisable Channels—Technical Steps, Current Status, and Review of Outcomes - Subramaniam, Ramnath (Frontiers in Pediatrics, 2019)
Purpose: To report the current status of Robotic approach to creation of CC with the author’s personal experience compared to published literature on technical steps, follow up and outcomes. Methods: CC data was extracted from the prospective database set up for all Robotic paediatric urology procedures performed by the author at his institution. A literature search was then performed to look at the evidence base. Results: 18 consecutive cases (8M:7F) of Robotic approach to creation of CC was identified and included. All attempted cases were successfully completed without any conversion to open approach. Median age at surgery was 10.75 years (IQR 6.9-16.5); Median OT 197 mins (IQR 131-295) with concomitant procedures in 4 cases. Appendix was used in 14 cases as CC conduit and distal ureter in 4 cases. Median LOS was 2.75 days (IQR 2-6) and Median FU 27.3m. Whilst FU duration is comparable to published series, average OT and LOS was much lower in this series. The LOS in this robotic series is much lower than the author’s experience with open approach (2.75 vs 5.8 days). No major complications postoperatively except for one exit site wound infection managed conservatively. None of the CC have been revised in this series and all channels are patent with 12F or 14 F admissible catheter size. There were no cases of incontinence related to technique of creation of CC and no incidence of exit site stomal stenosis with use of ACE stopper until channel matures and CIC is established. Conclusion: Robotic approach to CC is feasible, safe with excellent outcomes and minimum morbidity. Robotic complex bladder reconstructive surgery offers some advantages to children compared to open approach but is only currently performed in few tertiary centres with expertise.